Exploring depressive symptoms and its associates among Bangladeshi older adults amid COVID-19 pandemic: findings from a cross-sectional study - Mistry, Sabuj Kanti (Soc Psychiatry Psychiatr Epidemiol, 2021)
PURPOSE: Depression, one of the most common mental disorders, is up-surging worldwide amid the ongoing coronavirus disease 2019 (COVID-19) pandemic, especially among the older population. This study aims to measure prevalent depressive symptoms and its associates among older adults amid the COVID-19 pandemic in Bangladesh. METHODS: This cross-sectional study was carried out among 1032 older Bangladeshi adults, aged 60 years and above, through telephone interviews in October 2020. We used a semi-structured questionnaire to collect data on participants’ socio-demographic and lifestyle characteristics, pre-existing medical conditions, and COVID-19-related information. Meanwhile, depressive symptoms were measured using the 15-item Geriatric Depression Scale (GDS-15). The binary logistic regression model was used to identify the factors associated with depressive symptoms. RESULTS: Two-in-five participants showed depressive symptoms on the GDS-15 scale. Poor socioeconomic characteristic such as low family income, dependency on the family for living, recipient of financial support during the pandemic was associated with higher odds of depressive symptoms. Participants with pre-existing medical conditions had 91% higher odds of depressive symptoms. Social isolation, captured in terms of living alone (aOR = 2.11, 95% CI 1.11–4.01), less frequent communication during pandemic (aOR = 1.55, 95% CI 1.07–2.26), perceived loneliness (aOR = 2.25, 95% CI 1.47–3.45), and isolation from others (aOR = 2.45, 95% CI 1.62–3.70) were associated with higher odds of depressive symptoms. CONCLUSIONS: Our study found a sizeable proportion of study participants with depressive symptoms amidst the ongoing pandemic. The findings of the present study call for the urgent need for mental health support package targeting this vulnerable group of population.